DETERMINAN DETERMINAN BUDAYA ORGANISASI TERDAHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Muhammad Farhan Juliansya; Tasril Tasril; Murnawati Murnawati (Universitas Lancang Kuning, 2023)
Human resource â€œmanagement in an organization can be interpreted as supervising employees to ensure that they produce optimum performance in order to achieve organizational goals. Employee performance is the achievement of work results both in quality and quantity in carrying out their duties as their responsibilities. The research objective is to examine the influence of organizational culture on job satisfaction, as well as the influence of organizational culture and job satisfaction on employee performance at PT. Citra Intel Primary Pekanbaru. This study uses a quantitative and descriptive approach to see the causal relationship of the variables studied. The census method was used in taking a sample of 38 employees. PLS SEM analysis was used to evaluate the hypothesized model statistically using PLS software version 3.2.9, and to determine the extent to which the hypothesized model is consistent with the sample data. The findings of this study indicate that organizational culture has a positive and significant effect on job satisfaction. Organizational culture and job satisfaction each have a positive and significant effect on employee performance. Job satisfaction can function as an intervening variable for the relationship between organizational culture and employee performanceâ€ which shows a positive and significant influence